Employ Gamification to Make â€œI&CSâ€ More Interesting - Dixit, Rashmi K.; Nirgude, Manisha; Yalagi, Pratibha S. (Journal of Engineering Education Transformations, 2018)
The world of internet includes lot of viruses and hackers, eavesdropping and electronic fraud. So, there is a need of security to information and cyber data. The requirement is not only of secrecy but the authenticity of information is also equally important. The requirements of security and authenticity within an organization are on a boom now which has undergone lots of changes over the decades. Information and Cyber Security Course tries to provide both the principles and practice of cryptography and network security. The awareness and study of security issues is required. It plays major role in the industry and organization. Hence the course of Information&Cyber Security is a must for students to learn especially for Computer Scienece and Information Technology students. To create interest in learning this course, the fun learning activity like gamification is implemented. According to the Merriam-Webster dictionary, a game is â€œan activity engaged in for diversion or amusementâ€. Gamification in general speaking is a fun activity to engage the student, to meet learning objective. The Study proposes Gamification which provides a smart way of teaching to make learner active. The paper focuses on involvement and engagement of the learner with Gamification. The experiment is conducted for the final year Computer Science and Engineering students for the course of Information and Cyber Security. The results show that the ability of problem-solving among students increased effectively with more understanding level. The effectiveness of the experiment is verified by the survey from students and the university results.